Global trends and epidemiological shifts in gastrointestinal cancers: insights from the past four decades - Mengmeng Li; Sumei Cao; Rui‐Hua Xu (Cancer Communications)
Abstract Background The epidemiological profiles of gastrointestinal (GI) cancers vary across countries and over time, largely reflecting variations in risk factors and screening practices. We aimed to provide an overview of the current global burden of the five major types of GI cancers and conduct an updated evaluation of the long‐term trends of GI cancers. Methods The updated numbers of new cases and deaths, and age‐standardized rates (ASR), of the five GI cancers for 185 countries were sourced from the GLOBOCAN 2022, and presented by cancer site, continent, and human development index (HDI). For 43 countries, annual incidence and mortality data were obtained from the Cancer Incidence in Five Continents Plus and World Health Organization mortality databases, supplemented by the mortality data from the Disease Surveillance Points system for China. We compared the long‐term trends of ASRs across countries since 1980, and estimated average annual percent changes (AAPCs) for the recent period 2003‐2017. Results In 2022, there were 4,783,391 new cases and 3,235,719 deaths from the five GI cancers, accounting for 23.9% and 33.2% of all new cancer cases and deaths worldwide, respectively. Cancers of oesophagus, stomach, and liver were more common in Asian and high HDI countries, and colorectal and pancreatic cancer in western and very high HDI countries. Downward trends were observed in almost all countries for gastric cancer and most countries for oesophageal cancer. For colorectal cancer, the most favorable and unfavorable trends were found in 10 and 19 countries respectively. The largest decreases in liver cancer burden were mainly in eastern and southeastern Asia, while increases were seen in North America, Oceania, and Northern Europe, with AAPCs of 3%∼7% for incidence and 2%∼9% for mortality during 2003‐2017. Half of the included countries showed increases in pancreatic cancer burden, with the largest AAPCs in Cyprus, Thailand, India,Türkiye, France, and Belarus for incidence, and Türkiye, Thailand, and China for mortality. Conclusions Deviating patterns were found for GI cancers worldwide. Multi‐setting studies might provide insights into the underlying etiologies of these cancers, and identify areas where urgent cancer control strategies are needed.